The dendritic cell side of the immunological synapse - Verboogen Danielle R.J. (Biomolecular Concepts, 2016)
Immune responses are initiated by the interactions between antigen-presenting cells (APCs), such as dendritic cells (DCs), with responder cells, such as T cells, via a tight cellular contact interface called the immunological synapse. The immunological synapse is a highly organized subcellular structure that provides a platform for the presentation of antigen in major histocompatibility class I and II complexes (MHC class I and II) on the surface of the APC to receptors on the surface of the responder cells. In T cells, these contacts lead to highly polarized membrane trafficking that results in the local release of lytic granules and in the delivery and recycling of T cell receptors at the immunological synapse. Localized trafficking also occurs at the APC side of the immunological synapse, especially in DCs where antigen loaded in MHC class I and II is presented and cytokines are released specifically at the synapse. Whereas the molecular mechanisms underlying polarized membrane trafficking at the T cell side of the immunological synapse are increasingly well understood, these are still very unclear at the APC side. In this review, we discuss the organization of the APC side of the immunological synapse. We focus on the directional trafficking and release of membrane vesicles carrying MHC molecules and cytokines at the immunological synapses of DCs. We hypothesize that the specific delivery of MHC and the release of cytokines at the immunological synapse mechanistically resemble that of lytic granule release from T cells.